ECOTHEOLOGY AND FAMILY EDUCATION: INSTILLING ANTI-WASTE VALUES BASED ON QS AL-AN‘AM 6:141 IN PRESERVING THE ENVIRONMENT - Abu Rizki, Ahmad; Firman, (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
The environmental crisis demands a shift not only in technical aspects but also in moral-spiritual paradigms. This study explores the integration of Islamic ecotheology, family education, and the normative message of QS al-An‘am 6:141 as the foundation for developing anti-waste character within Muslim families. Using a qualitative approach with library research methods and thematic content analysis, this study examines classical-modern interpretations of QS al-An‘am 6:141 and relevant academic literature related to tauhid, khalifah, mizan, and istishlah as the basis of Islamic ecotheology. The findings reveal that QS al-An‘am 6:141 emphasizes the principle of moderation in consumption and the prohibition of israf (excessiveness) as a theological framework for maintaining the sustainability of natural resources. In practice, the family is proven to be the primary space for internalizing values through parental role modeling, daily habituation, and direct teaching, thereby shaping sustainable consumption patterns and fostering ecological awareness in children from an early age. This study offers an integrative model of faith-action that positions environmentally friendly practices as an expression of obedience to Allah and strengthens the family’s role as an agent of ecological change. The study emphasizes the importance of developing family education based on Islamic ecotheology to encourage anti-waste and sustainable behavior.